64 An Audit of Same Day Theatre List Cancellations. (28th February 2022) - Ramjeeawon, A.; Bulstrode, N.
Abstract: Introduction: Given the reduction in elective operating during the Covid pandemic, efficient use of theatre time is paramount to reduce elective waiting list times. The aims of this audit were to identify the proportion of patients who were cancelled from theatre lists on the day, reasons for cancellation, and the proportion of patients who were cancelled due to non-adherence to pre-operative fasting rules. Method: The previous 30 patients on a single surgeon's elective operating list were reviewed using electronic patient records, admissions teams list, and surgeon recall to identify numbers of and reasons for on the day cancellations. The standards used were the perioperative fasting in adults and children guideline from the European Society of Anaesthesiology, and a local trust guideline on pre-operative fasting. Results: 30 patients had been scheduled for elective surgery on a single surgeon's paediatric plastic surgery list between April and May 2021. 3 patients (10%) cancelled on the day of their planned procedures. Of these patients cancelling on the day, 2 (66%) cancelled due to non-adherence to pre-operative fasting rules, 1 (33%) cancelled due to parents choosing to defer the operation. Conclusions: Non-adherence to pre-operative fasting rules was an important reason for on the day cancellations on this elective operating list. A pre-operative fasting information sheet was developed for patients and parents to explain the fasting rules and timings. Once sufficient patients and parents receive the information sheet, the audit will be repeated. If successful, it may be sent to patients and parents for all elective operating lists.